Comparison of Postoperative Analgesic Effect of Dexamethasone and Fentanyl Added to Lidocaine through Axillary Block in Forearm Fracture. (29th December 2013) - Yaghoobi, Siamak; Seddighi, Mahyar; Yazdi, Zohreh; Ghafouri, Razieh; Khezri, Marzieh Beigom
Abstract : Aim . Regional analgesia has been introduced as better analgesic technique compared to using systemic analgesic agents, and it may decrease the adverse effects of them and increase the degree of satisfaction. Several additives have been suggested to enhance analgesic effect of local anesthetic agents such as opioids and steroids. We designed this randomized double-blind controlled study to compare the analgesic efficacy of the dexamethasone and fentanyl added to lidocaine using axillary block in patients undergoing operation of forearm fracture. Materials and Methods . Seventy-eight patients 20–60 years old were recruited in a prospective, double-blinded, randomized way. Axillary block was performed in the three groups by using 40 mL lidocaine and 2 mL distilled water (L group), 40 mL lidocaine and 2 mL dexamethasone (LD group), and 40 mL lidocaine and 2 mL fentanyl (LF group). The onset time of sensory and motor block, duration of sensory and motor block, the total analgesic dose administered during 6 hours after the surgery, and hemodynamic variables were recorded. Results . The duration of sensory and motor block was significantly longer in LD group compared to other groups (P < 0.001 ). Similarly, the total analgesic consumption in LD group was smaller compared to other groups (P < 0.001 ). Comparison of hemodynamic consequences of axillary block and surgery failed to reveal any statistically significant differences between all groups. Conclusion . Addition of dexamethasone to lidocaine significantly prolonged the duration of analgesia compared with fentanyl/lidocaine mixture or lidocaine alone using axillary block in patients undergoing forearm fracture surgery. This trial is registered withIRCT2012120711687N1 .